PERAN DAN UPAYA ORANG TUA DALAM MENANAMKAN SIKAP RESILIENSI ANAK USIA 4-6 TAHUN - Roro Nasroh Latifah; Maila D.H. Rahiem (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
This study investigated the influence and efforts of parents in building resilience in children ages 4-6. This investigation employed qualitative exploratory methods. Researchers gathered information through interviews and documentation procedures. Researchers interviewed 19 parents in the Cikande, Serang, Banten area who have children aged 4 to 6 years. According to the data, parents instilled a resilient attitude in their children by: 1) teaching children the meaning of loss; 2) demonstrating to children how to be patient during disasters/misfortunes; 3) providing a sense of security and comfort so that children feel they always have support and strength; 4) instilling in their children the belief that they can overcome adversity; and 5) encouraging their children to persevere in the face of hardship. This study recommends that parents continue to become more conscious of the importance of instilling a resilient attitude in children, and that educators and educational institutions continue to organize outreach programs for strategies to instill a resilient attitude in children from a young age.